Ziconotide-Induced Oro-lingual Dyskinesia: 3 Cases. (6th October 2020) - Grajny, Kristopher; Durphy, Jennifer; Adam, Octavian; Azher, Sharmeen; Gupta, Megan; Molho, Eric
Background: Ziconotide (ZCN), a nonopioid analgesic, is first-line intrathecal therapy for patients with severe chronic pain refractory to other management options. We describe three cases of ZCN-induced movement disorders. Cases: Case one is a 64-year-old woman who presented with oro-lingual (OL) dyskinesia with dysesthesias and bilateral upper extremity kinetic tremor. Case two is a 43-year-old man with a 20-month history of ZCN treatment who developed OL dyskinesia with dysesthesias, involuntary left hand and neck movements, hallucinations, dysesthesias on his feet, and gait imbalance. Case three is a 70-year-old man with a 4-month history of ZCN use who developed OL dyskinesia with dysesthesias. Conclusions: Intrathecal treatment of pain with ZCN may be complicated by a drug-induced movement disorder where OL dyskinesia is characteristic. The movement disorder is likely to be dose related and reversible with ZCN discontinuation, but a chronic movement disorder is also possible.